Antibacterial medical primary packaging coated paper, preparation method and application

CN122980272APending Publication Date: 2026-10-27MEDICO (SHANGHAI) PACKAGING MATERIALS CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610915206.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

尤其在潮湿、常温仓储环境下,微生物大量滋生,部分细菌可穿透涂胶纸的微孔隙或沿胶层边缘渗入包装内部,造成医疗器械的二次污染

Benefits of technology

[0016]本发明的优点和有益效果在于:将底层密封与表层抗菌功能分离,底层较厚的改性密封胶层提供了剥离强度和耐灭菌腐蚀能力,表层较薄的抗菌胶层则赋予材料长效广谱抗菌活性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses antibacterial medical primary packaging coated paper, a preparation method and application, and the coated paper comprises a medical breathable base paper substrate, a bottom modified sealant layer and a surface antibacterial protective glue layer. The bottom modified sealant layer is coated on the upper surface of the substrate, and the surface antibacterial protective glue layer is coated on the surface of the bottom glue layer, so as to form a double-layer gradient coated structure. The surface antibacterial protective glue layer comprises a composite antibacterial agent and a pore-forming dispersant, the pore-forming dispersant is a gel substance loaded with an azo compound, and the azo compound forms an electrostatic adsorption complex with chitosan. In the preparation process, double-layer gradient coating is firstly performed, and then low-temperature excitation treatment is performed at 50-70 DEG C, so that the electrostatic adsorption between the azo compound and the chitosan is destroyed, the azo compound is uniformly released and dispersed, and a micro-porous structure is formed at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical packaging materials technology, specifically to an antibacterial coated paper for the initial sterilization packaging of medical devices, its manufacturing method, and its application. Background Technology

[0002] Aseptic packaging of medical devices is a crucial step in ensuring patient safety and preventing nosocomial cross-infection. The primary sterilization packaging comes into direct contact with the medical device and must simultaneously meet multiple stringent requirements throughout the sterilization, storage, transportation, and clinical preparation processes, including microbial barrier properties, sterilization gas penetration, physical strength, and biocompatibility. Coated paper, due to its excellent breathability, heat-sealability, and cost-effectiveness, is widely used for the primary sterilization packaging of disposable medical devices such as syringes, surgical gloves, dressings, and catheters.

[0003] Ordinary coated paper relies solely on physical barriers to prevent microorganisms and does not possess antibacterial or bactericidal capabilities. During production, storage, transportation, and clinical use, bacteria, mold, and other microorganisms easily adhere to the packaging surface. Especially in humid, ambient-temperature storage environments, microorganisms proliferate rapidly, and some bacteria can penetrate the micropores of the coated paper or seep into the packaging along the edges of the adhesive layer, causing secondary contamination of medical devices. Conventional adhesive layers often use acrylic or hot melt adhesive systems, which lack sufficient resistance to high temperatures and sterilization corrosion. Common sterilization methods for medical devices include 134°C high-temperature and high-pressure steam sterilization and ethylene oxide gas sterilization. After multiple sterilization cycles, the adhesive layer is prone to cracking, peeling, stickiness, and discoloration, leading to packaging seal failure, abnormal air permeability, and even damage to the sterile barrier. Summary of the Invention

[0004] The object of the present invention is to overcome at least one of the problems shown in the background art.

[0005] To achieve the above objectives, the technical solution provided by the present invention is as follows.

[0006] An antibacterial medical primary packaging coated paper, comprising: Medical breathable base paper substrate; A bottom modified sealant layer coated on the upper surface of the medical breathable base paper substrate; A surface antibacterial protective adhesive layer is applied to the surface of the underlying modified sealant layer; The bottom modified sealant layer and the top antibacterial protective adhesive layer form a double-layer gradient coating structure; The overall air permeability of the coated paper is 200-400 s / 100ml, and the seal peel strength is 8-15 N / 15mm; The medical breathable base paper is medical-grade pure cotton fiber breathable paper with a basis weight of 60-80 g / m² and a longitudinal wet tensile strength ≥3.5 kN / m.

[0007] Optionally, the underlying modified sealant layer comprises, by weight, the following components: Modified acrylic resin: 45-55 parts; Medical hot melt elastomer: 20-25 parts; Crosslinking agent: 3-5 parts; Toughening agent: 2-4 parts; Deionized water: 15-20 parts; The crosslinking agent is a medical-grade epoxy crosslinking agent, and the toughening agent is a polyether-type medical toughening agent.

[0008] Optionally, the surface antibacterial protective adhesive layer comprises, by weight, the following components: Waterborne polyurethane resin: 50-60 parts; Compound antibacterial agent: 4-8 parts; Pore-forming dispersant: 2-3 parts; Film-forming aid: 1-2 parts; Deionized water: 18-22 parts; The composite antibacterial agent is composed of nano titanium dioxide, chitosan and silver ion slow-release antibacterial powder in a mass ratio of (2-4):(4-6):(1-3).

[0009] Optionally, the pore-forming dispersant is a gel material supported on an azo compound, wherein the mass ratio of the gel material to the azo compound is (3-5):1.

[0010] Optionally, the coating amount of the bottom modified sealant layer is 8-12 g / m², and the coating amount of the top antibacterial protective adhesive layer is 3-5 g / m².

[0011] A method for preparing an antibacterial medical primary packaging coated paper, characterized by comprising the following steps: S1. Dry the medical breathable base paper substrate at 60-70℃ for 30 minutes; S2. After mixing and stirring the modified acrylic resin, medical hot melt elastomer, and deionized water, add the crosslinking agent and toughening agent, and then perform high-speed homogenization and emulsification. S3. After mixing waterborne polyurethane resin and deionized water, film-forming aid and composite antibacterial agent are added, and then a gel-loaded azo compound as a pore-forming dispersant is added. The gel-loaded azo compound forms an electrostatic adsorption complex with chitosan, and is then dispersed at high speed and defoamed by ultrasonication. S4. First, apply the base layer sealant and pre-dry and cure it; then apply the top layer antibacterial sealant. S5. Heat treatment of the coated semi-finished product at 50-70℃ to break the electrostatic adsorption between the azo compound and chitosan, so that the azo compound is uniformly released and dispersed in the adhesive layer, and at the same time, a microporous structure is formed. S6. First cure at 90℃ for 20 minutes, then cure at 120℃ for 15 minutes; S7. Perform dust-free cooling, electrostatic dust removal, and surface smoothing treatment on the cured coated paper.

[0012] Optionally, in step S2, the high-speed homogenization emulsification rotation speed is 8000 r / min and the time is 20 minutes.

[0013] Optionally, in step S5, the heating treatment time is 5-15 minutes.

[0014] Optionally, in S7, the surface leveling treatment is carried out using a contact hot press roller or an air flotation leveling device.

[0015] Application of antibacterial medical primary packaging coated paper in the preparation of sterilization packaging materials for medical devices.

[0016] The advantages and beneficial effects of this invention are as follows: the bottom sealing layer is separated from the surface antibacterial function, the thicker modified sealant layer at the bottom provides peel strength and resistance to sterilization and corrosion, while the thinner antibacterial layer at the surface endows the material with long-lasting broad-spectrum antibacterial activity.

[0017] This invention introduces a gel material loaded with an azo compound as a pore-forming dispersant into the surface adhesive layer. Utilizing the electrostatic adsorption between the azo compound and chitosan, the antibacterial components are stably dispersed during the adhesive preparation stage. A low-temperature activation treatment after coating disrupts this electrostatic adsorption balance, allowing the azo compound to be uniformly released and simultaneously forming micron-sized breathable pores. This achieves suitable and controllable air permeability without sacrificing sealing performance. It can withstand repeated high-temperature steam sterilization at 134℃ and ethylene oxide sterilization more than 10 times without cracking, peeling, or stickiness of the adhesive layer; the peel strength reaches 8-15 N / 15 mm; biocompatibility testing is satisfactory; and it exhibits no cytotoxicity, skin irritation, or sensitization. Detailed Implementation

[0018] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application are described in detail below. It is to be understood that the specific embodiments described herein are merely illustrative of this application and not intended to limit it. All other embodiments obtained by those skilled in the art based on the embodiments in this application without inventive effort are within the scope of protection of this application.

[0019] The terms “comprising” and “having”, and any variations thereof, used in this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not limited to the steps or units listed, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to such process, method, product, or apparatus.

[0020] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly or implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0021] This invention provides an antibacterial medical primary packaging coated paper, comprising a medical breathable base paper substrate, a bottom modified sealant layer coated on the upper surface of the medical breathable base paper substrate, and a top antibacterial protective adhesive layer coated on the surface of the bottom modified sealant layer. The bottom modified sealant layer and the top antibacterial protective adhesive layer form a double-layer gradient coating structure. The overall air permeability of the coated paper is 200-400s / 100ml, and the seal peel strength is 8-15N / 15mm. The medical breathable base paper substrate is medical-grade pure cotton fiber breathable paper with a basis weight of 60-80g / ㎡ and a longitudinal wet tensile strength ≥3.5kN / m.

[0022] This invention spatially separates the sealing and antibacterial functions. The thicker bottom adhesive layer provides primary sealing and adhesion, as well as resistance to sterilization corrosion; the thinner top adhesive layer provides antibacterial protection and breathability control. The two adhesive layers are bonded to the paper surface during segmented curing, forming a unified structure. Overall breathability is controlled within the range of 200-400 s / 100ml, ensuring rapid penetration of ethylene oxide or high-temperature steam into the packaging during sterilization while effectively blocking external microorganisms and moisture intrusion during normal storage. A peel strength of 8-15 N / 15mm ensures that the heat-sealed packaging will not delaminate due to mechanical force during transportation and use. The basis weight of the medical-grade pure cotton fiber breathable paper is controlled at 60-80 g / m². Too low a basis weight results in insufficient substrate strength, making it difficult to achieve a longitudinal wet tensile strength of over 3.5 kN / m, leading to easy breakage in humid sterilization environments; too high a basis weight reduces breathability, hindering the penetration of sterilizing gases and increasing packaging material costs and waste.

[0023] In some embodiments, the underlying modified sealant layer comprises, by weight: 45-55 parts modified acrylic resin, 20-25 parts medical hot melt elastomer, 3-5 parts crosslinking agent, 2-4 parts toughening agent, and 15-20 parts deionized water. The crosslinking agent is a medical-grade epoxy crosslinking agent, and the toughening agent is a polyether-type medical toughening agent.

[0024] The formulation of the bottom adhesive layer uses modified acrylic resin as the main film-forming material. Its molecular chain contains polar groups such as carboxyl and hydroxyl groups, which can form hydrogen bonds with the cellulose substrate to provide adhesion.

[0025] Pure acrylate systems are prone to ester bond hydrolysis under 134°C high-temperature steam sterilization conditions, leading to molecular chain breakage and sticky adhesive layers. This invention introduces a medical-grade epoxy crosslinking agent. During high-temperature curing, the epoxy groups in the epoxy crosslinking agent undergo ring-opening addition reactions with the carboxyl groups in the acrylic resin, forming a three-dimensional network structure. The polyether-type toughening agent addresses the brittleness problem caused by high crosslinking density, exhibiting excellent flexibility. When the adhesive layer is subjected to external force or internal stress generated by alternating hot and cold temperatures, these flexible segments can absorb and dissipate stress energy through conformational changes, preventing crack propagation.

[0026] In some embodiments, the surface antibacterial protective adhesive layer comprises, by weight: 50-60 parts of waterborne polyurethane resin, 4-8 parts of composite antibacterial agent, 2-3 parts of pore-forming dispersant, 1-2 parts of film-forming aid, and 18-22 parts of deionized water. The composite antibacterial agent is composed of nano-titanium dioxide, chitosan, and silver ion slow-release antibacterial powder in a weight ratio of (2-4):(4-6):(1-3).

[0027] Waterborne polyurethane resin, used as a carrier resin, contains urethane bonds and ionic groups in its molecular chain, exhibiting excellent film-forming properties, flexibility, and biocompatibility. The soft segments in the polyurethane molecular chain impart flexibility to the adhesive layer, while the hard segments provide mechanical strength. This microphase separation structure allows the surface adhesive layer to adhere tightly to the underlying layer without cracking. The composite antibacterial agent employs a compound system with three antibacterial mechanisms, achieving broad-spectrum inhibition against common pathogenic bacteria such as Escherichia coli, Staphylococcus aureus, and Candida albicans. Nano-titanium dioxide, under ambient light, can generate photogenerated electrons and holes. These high-energy charge carriers react with adsorbed oxygen and water molecules on the surface to generate superoxide anion radicals and hydroxyl radicals. These reactive oxygen species possess extremely strong oxidizing power, capable of damaging unsaturated fatty acids in bacterial cell membranes, oxidizing sulfhydryl groups in proteins, and bases in DNA chains, leading to bacterial inactivation. Chitosan is a natural cationic polysaccharide. Under weakly acidic or neutral conditions, the amino groups on its molecular chain are protonated. The positively charged chitosan molecules electrostatically attract the negatively charged bacterial cell membrane, leading to localized charge neutralization and structural disorder, increased membrane permeability, and leakage of intracellular proteins and nucleic acids. Simultaneously, low-molecular-weight components of chitosan can penetrate the cell membrane and enter the cell, binding to DNA and inhibiting transcription. Silver ion slow-release antibacterial powder slowly releases Ag through an ion exchange mechanism. + It induces bacteria to produce intracellular reactive oxygen species, causing oxidative stress damage.

[0028] In some embodiments, the pore-forming dispersant is a gel material supported on an azo compound, and the mass ratio of the gel material to the azo compound is (3-5):1.

[0029] In the preparation stage of the adhesive, a gel material (preferably negatively charged natural polysaccharides such as sodium alginate and carboxymethyl cellulose) is loaded with an azo compound. This complex forms a stable core-shell complex with chitosan through electrostatic adsorption. Specifically, the carboxyl groups on the gel material molecular chain are negatively charged in weakly alkaline or neutral aqueous systems, while the amino groups on the chitosan molecular chain are positively charged, and the two undergo electrostatic self-assembly. At the same time, the azo compound is encapsulated in the hydrophobic microdomains of the gel material, forming a loaded structure. The steric hindrance effect of the complex can effectively isolate the nano-titanium dioxide particles and silver ion slow-release powder in the composite antibacterial agent, preventing agglomeration; the electrostatic repulsion of the complex maintains the colloidal stability of the antibacterial adhesive, avoiding sedimentation and stratification; and thirdly, the azo compound is temporarily encapsulated in the gel material and will not be released prematurely during the storage and coating process of the adhesive.

[0030] In the low-temperature activation treatment step after coating, the azo compound is activated by heat. The N=N double bonds of the azo compound undergo homolytic cleavage or intramolecular rotation at 50-70°C, disrupting the coating bond between it and the gel material. Simultaneously, the electrostatic adsorption equilibrium is also broken due to increased thermal motion. The azo compound is uniformly released from the gel material and diffuses throughout the entire surface adhesive layer, creating an in-situ pore-forming effect. The volume originally occupied by the azo compound becomes vacancies after release, with vacancies ranging in size from tens to hundreds of nanometers. These vacancies are retained during the subsequent high-temperature curing process, forming through- or semi-through micropermeable channels. Unlike traditional physical or chemical foaming agents, the low-temperature activation pore-forming technology of this invention achieves uniform pore distribution and controllable pore size through the electrostatic adsorption and thermally activated desorption mechanisms between the azo compound and chitosan.

[0031] In some embodiments, the coating amount of the bottom modified sealant layer is 8-12 g / m², and the coating amount of the top antibacterial protective adhesive layer is 3-5 g / m².

[0032] The choice of coating amount is based on a comprehensive consideration of functional division and cost optimization. A thicker underlayer adhesive layer is necessary because sealing and sterilization corrosion resistance require sufficient thickness to provide mechanical strength and cross-link network integrity. When the coating amount is below 8 g / m², the underlayer adhesive layer may not completely cover the fiber gaps on the substrate surface, resulting in insufficient sealing. When the coating amount is above 12 g / m², it not only increases material costs but also leads to excessively thick adhesive layers with low air permeability, affecting the penetration of sterilization gases.

[0033] This invention also provides a method for preparing antibacterial medical primary packaging coated paper, comprising the following steps: S1. Dry the medical breathable base paper substrate at 60-70℃ for 30 minutes; S2. After mixing and stirring the modified acrylic resin, medical hot melt elastomer, and deionized water, add the crosslinking agent and toughening agent, and then perform high-speed homogenization and emulsification. S3. After mixing waterborne polyurethane resin and deionized water, film-forming aid and composite antibacterial agent are added, and then a gel-loaded azo compound as a pore-forming dispersant is added. The gel-loaded azo compound forms an electrostatic adsorption complex with chitosan, and is then dispersed at high speed and defoamed by ultrasonication. S4. First, apply the base layer sealant and pre-dry and cure it; then apply the top layer antibacterial sealant. S5. Heat treatment of the coated semi-finished product at 50-70℃ to break the electrostatic adsorption between the azo compound and chitosan, so that the azo compound is uniformly released and dispersed in the adhesive layer, and at the same time, a microporous structure is formed. S6. First cure at 90℃ for 20 minutes, then cure at 120℃ for 15 minutes; S7. Perform dust-free cooling, electrostatic dust removal, and surface smoothing treatment on the cured coated paper.

[0034] In S5, the coated semi-finished product is heated at 50-70℃ for 5-15 minutes. This temperature range is chosen based on the thermodynamic considerations of the thermal decomposition kinetics and electrostatic adsorption equilibrium of the azo compound. Below 50℃, the azo compound decomposes at a very low rate, and the molecules exist in a stable trans conformation, resulting in a relatively strong bond with the gel material. When the temperature rises to 50-70℃, the intramolecular rotation of the azo compound intensifies, some molecules undergo cis-trans isomerization, and the electron cloud density of the N=N double bond changes, leading to a weakening of its interaction with the gel material. Simultaneously, the increased thermal motion causes the chitosan molecular chains to extend further, lowering the equilibrium constant of electrostatic adsorption. The azo compound is then released from the gel material and diffuses into the gel layer.

[0035] In some embodiments, the high-speed homogenization emulsification speed in S2 is 8000 r / min, and the time is 20 minutes. This parameter combination has been optimized and verified: if the speed is too low or the time is too short, nanoscale uniform dispersion cannot be formed, and the crosslinking agent and toughening agent will exist in the form of larger droplets, which will lead to uneven crosslinking and reduced toughening effect; if the speed is too high, too much heat will be generated, which may lead to increased pre-crosslinking and viscosity of the adhesive.

[0036] In some embodiments, the heat treatment time in S5 is 5-15 minutes. As mentioned earlier, the treatment time is inversely related to the excitation temperature: at lower excitation temperatures, a longer time is required to achieve sufficient azo compound release; at higher excitation temperatures, a shorter time is sufficient for release. The selection of the treatment time also needs to consider the speed matching of the production line; generally, higher temperatures and shorter times are preferred in production to improve production efficiency.

[0037] In some embodiments, the surface leveling treatment in S7 is performed using a contact-type hot press roller or an air-float leveling device. Each device has its applicable scenarios: the contact-type hot press roller is suitable for continuous mass production, offering high efficiency and low equipment cost, but it involves some thermal contact with the adhesive surface; the air-float leveling device is suitable for products with high surface quality requirements, such as those used for packaging precision surgical instruments.

[0038] The present invention will be further described and illustrated below with reference to specific embodiments. It should be noted that all reagents used in the embodiments of this application are commercially available. In the following embodiments, the modified acrylic resin is selected from the NeoCryl series of waterborne acrylic emulsions from DSM, the medical hot melt elastomer is selected from the BYNEL series of copolyester hot melt resins from DuPont, the crosslinking agent is Epoxoft 3M, a medical-grade epoxy crosslinking agent from Sartorius, and the toughening agent is VORANOL polyether polyol from Dow Chemical. The waterborne polyurethane resin is selected from the Bayhydrol series from Covestro. In the gel material loaded with the azo compound, the gel material is sodium alginate, and the azo compound is azobisisobutyronitrile (AIBN), which are loaded at a mass ratio of 4:1. The film-forming aid is dipropylene glycol butyl ether.

[0039] Example 1 S1. Place the medical-grade pure cotton fiber breathable paper substrate with a weight of 70g / ㎡ in a dust-free constant temperature workshop and dry it at 65℃ for 30 minutes.

[0040] S2. Weigh 50 parts of modified acrylic resin, 22 parts of medical hot melt elastomer, and 18 parts of deionized water according to the mass ratio. Stir at a low speed of 300 r / min for 15 minutes. Then add 4 parts of crosslinking agent and 3 parts of toughening agent. Homogenize and emulsify at a high speed of 8000 r / min for 20 minutes.

[0041] S3. Weigh 55 parts of waterborne polyurethane resin and 20 parts of deionized water by weight, mix them, add 1.5 parts of film-forming aid and 6 parts of composite antibacterial agent (nano titanium dioxide: chitosan: silver ion slow-release antibacterial powder mass ratio 3:5:2), stir evenly, add 2.5 parts of pore-forming dispersant, disperse at 1500r / min for 30 minutes, and then defoam by ultrasonication for 10 minutes.

[0042] S4. Apply the base sealant to the surface of the base paper using a textured coating machine with a coating amount of 10g / ㎡, and pre-dry at 80℃ for 3 minutes; then apply the surface antibacterial sealant to the surface of the base sealant layer with a coating amount of 4g / ㎡.

[0043] S5. Send the coated semi-finished product into a 60℃ heating channel for 10 minutes.

[0044] S6. First, cure in a 90℃ oven for 20 minutes, then raise the temperature to 120℃ and cure for 15 minutes.

[0045] S7. After the cured adhesive paper is cooled to room temperature in a dust-free environment, it is then subjected to electrostatic dust removal and surface smoothing treatment using a contact hot press roller (roller temperature 40℃, linear pressure 2kg / cm). The finished product is then cut.

[0046] The coated paper prepared in this embodiment has an air permeability of 285s / 100ml and a peel strength of 12.3N / 15mm. Its antibacterial properties were tested according to GB / T20944.3-2008 standard, showing a 24-hour antibacterial rate of 99.96% against *Escherichia coli* (ATCC 8739), 99.92% against *Staphylococcus aureus* (ATCC 6538), and 99.88% against *Candida albicans* (ATCC 10231). After accelerated aging at 40℃ and 75% relative humidity for 6 months (equivalent to 18 months at room temperature), the antibacterial rates were 99.4%, 99.3%, and 99.1%, respectively.

[0047] Example 2 The difference between this embodiment and Embodiment 1 is as follows: In S2, there are 45 parts of modified acrylic resin, 25 parts of medical hot melt elastomer, 20 parts of deionized water, 5 parts of crosslinking agent, and 4 parts of toughening agent; in S3, there are 50 parts of waterborne polyurethane resin, 18 parts of deionized water, 1 part of film-forming aid, 8 parts of composite antibacterial agent (mass ratio 4:5:1), and 3 parts of pore-forming dispersant; in S4, the bottom coating amount is 12 g / ㎡ and the top coating amount is 5 g / ㎡; in S5, the activation temperature is 50℃ and the treatment time is 15 minutes.

[0048] The coated paper prepared in this embodiment has an air permeability of 335s / 100ml and a peel strength of 14.1N / 15mm. Antibacterial performance tests showed an antibacterial rate of 99.91% against Escherichia coli, 99.88% against Staphylococcus aureus, and 99.82% against Candida albicans. After 10 cycles of high-temperature steam sterilization at 134℃, the adhesive surface showed no cracking, peeling, or stickiness, and the peel strength retention rate was 92.6%.

[0049] Example 3 The difference between this embodiment and Embodiment 1 is as follows: In S2, there are 55 parts of modified acrylic resin, 20 parts of medical hot melt elastomer, 15 parts of deionized water, 3 parts of crosslinking agent, and 2 parts of toughening agent; in S3, there are 60 parts of waterborne polyurethane resin, 22 parts of deionized water, 2 parts of film-forming aid, 4 parts of composite antibacterial agent (mass ratio 2:6:2), and 2 parts of pore-forming dispersant; in S4, the undercoat amount is 8 g / m², and the surface coating amount is 3 g / m²; in S5, the excitation temperature is 70℃, and the treatment time is 5 minutes; in S7, the surface leveling treatment uses an air-floating leveling device and does not use a hot press roller.

[0050] The coated paper prepared in this embodiment has an air permeability of 210s / 100ml and a peel strength of 8.8N / 15mm. Antibacterial performance tests showed an antibacterial rate of 99.98% against Escherichia coli, 99.95% against Staphylococcus aureus, and 99.91% against Candida albicans. After 10 cycles of high-temperature steam sterilization at 134℃, the adhesive surface showed no cracking, peeling, or stickiness, and the peel strength retention rate was 90.1%.

[0051] Example 4 The difference between this embodiment and embodiment 1 is that the ratio of the composite antibacterial agent in S3 is adjusted to nano titanium dioxide: chitosan: silver ion slow-release antibacterial powder = 3:6:1.

[0052] The coated paper prepared in this embodiment has an air permeability of 278s / 100ml and a peel strength of 11.9N / 15mm. Antibacterial performance tests showed an antibacterial rate of 99.94% against Escherichia coli, 99.97% against Staphylococcus aureus, and 99.89% against Candida albicans. After 10 cycles of high-temperature steam sterilization at 134℃, the adhesive surface showed no cracking, peeling, or stickiness, and the peel strength retention rate was 93.1%.

[0053] Example 5 The difference between this embodiment and embodiment 1 is that the amount of crosslinking agent in S2 is increased to 5 parts and the amount of toughening agent is increased to 4 parts.

[0054] The coated paper prepared in this embodiment has an air permeability of 292s / 100ml and a peel strength of 13.6N / 15mm. Antibacterial performance tests showed an antibacterial rate of 99.93% against *Escherichia coli*, 99.91% against *Staphylococcus aureus*, and 99.85% against *Candida albicans*. After 10 cycles of high-temperature steam sterilization at 134℃, the adhesive layer surface showed no cracking, peeling, or stickiness, and the peel strength retention rate was 95.8%. Furthermore, after 10 cycles of ethylene oxide sterilization, the adhesive layer showed no stickiness or discoloration, and the peel strength retention rate was 95.3%.

[0055] Example 6 The difference between this embodiment and Example 1 is that the amount of pore-forming dispersant in S3 is increased to 3 parts, and the loading ratio of gel material to azo compound is adjusted to 3:1.

[0056] The coated paper prepared in this embodiment has an air permeability of 378s / 100ml and a peel strength of 10.5N / 15mm. Antibacterial performance tests showed an antibacterial rate of 99.90% against Escherichia coli, 99.87% against Staphylococcus aureus, and 99.80% against Candida albicans. After 10 cycles of high-temperature steam sterilization at 134℃, the adhesive layer surface showed no cracking, peeling, or stickiness, and the peel strength retention rate was 91.2%.

[0057] Comparative Example 1 The difference between this comparative example and Example 1 is that no pore-forming dispersant is added in S3 (i.e., the gel material loaded with azo compound is omitted).

[0058] The coated paper prepared in this comparative example has an air permeability of 95s / 100ml and a peel strength of 10.8N / 15mm. Antibacterial performance testing showed an antibacterial rate of approximately 65% ​​against Escherichia coli, approximately 62% against Staphylococcus aureus, and approximately 58% against Candida albicans, with significant intra-batch fluctuations. After 10 cycles of high-temperature steam sterilization at 134℃, the peel strength retention rate was 85.3%.

[0059] Comparative Example 2 The difference between this comparative example and Example 1 is that step S5 is omitted, that is, after coating, low-temperature activation treatment is not performed, and it directly proceeds to step S6 for segmented curing.

[0060] The coated paper prepared in this comparative example had an air permeability of 118 s / 100 ml and a peel strength of 10.5 N / 15 mm. Antibacterial performance testing showed an antibacterial rate of approximately 72% against Escherichia coli, approximately 70% against Staphylococcus aureus, and approximately 68% against Candida albicans, with significant batch-to-batch fluctuations. After 10 cycles of high-temperature steam sterilization at 134℃, the peel strength retention rate was 87.6%. After 3 months of accelerated aging, white spots of antibacterial agent precipitated on the adhesive layer surface, identified as a complex of silver ions and chitosan.

[0061] Comparative Example 3 The difference between this comparative example and Example 1 is that the double-layer gradient coating in S4 is changed to a single-layer coating, that is, the bottom sealant and the top antibacterial adhesive are pre-mixed and then coated in one go, with a total coating amount of 14g / ㎡.

[0062] The coated paper prepared in this comparative example has an air permeability of 175s / 100ml and a peel strength of 5.2N / 15mm. Antibacterial performance tests showed an antibacterial rate of 88% against Escherichia coli, 86% against Staphylococcus aureus, and 82% against Candida albicans. After 10 cycles of high-temperature steam sterilization at 134℃, the adhesive layer became noticeably sticky, and the peel strength retention rate was 40.4%.

[0063] Comparative Example 4 The difference between this comparative example and Example 1 is that the segmented curing in S6 is replaced with one-step high-temperature curing (curing at 120°C for 35 minutes).

[0064] The coated paper prepared in this comparative example exhibits numerous air bubbles and large pores within the adhesive layer, resulting in an air permeability of 560 s / 100 ml and a peel strength of 7.1 N / 15 mm. Antibacterial performance tests show an antibacterial rate of 97.2% against Escherichia coli, 96.8% against Staphylococcus aureus, and 95.9% against Candida albicans. After 10 cycles of high-temperature steam sterilization at 134℃, the peel strength retention rate is 72.3%.

[0065] Comparative Example 5 The difference between this comparative example and Example 1 is that chitosan is not added to the composite antibacterial agent; only nano-titanium dioxide and silver ion slow-release antibacterial powder (mass ratio 3:2) are used.

[0066] The coated paper prepared in this comparative example has an air permeability of 301s / 100ml and a peel strength of 11.2N / 15mm. Antibacterial performance tests showed an antibacterial rate of 82% against Escherichia coli, 79% against Staphylococcus aureus, and 75% against Candida albicans. After 10 cycles of high-temperature steam sterilization at 134℃, the peel strength retention rate was 91.5%.

[0067] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. An antibacterial medical primary packaging coated paper, characterized in that, include: Medical breathable base paper substrate; A bottom modified sealant layer coated on the upper surface of the medical breathable base paper substrate; A surface antibacterial protective adhesive layer is applied to the surface of the underlying modified sealant layer; The bottom modified sealant layer and the top antibacterial protective adhesive layer form a double-layer gradient coating structure; The overall air permeability of the coated paper is 200-400 s / 100ml, and the seal peel strength is 8-15 N / 15mm; The medical breathable base paper is medical-grade pure cotton fiber breathable paper with a basis weight of 60-80 g / m² and a longitudinal wet tensile strength ≥3.5 kN / m.

2. The antibacterial medical primary packaging coated paper according to claim 1, characterized in that, The underlying modified sealant layer comprises, by weight, the following components: Modified acrylic resin: 45-55 parts; Medical hot melt elastomer: 20-25 parts; Crosslinking agent: 3-5 parts; Toughening agent: 2-4 parts; Deionized water: 15-20 parts; The crosslinking agent is a medical-grade epoxy crosslinking agent, and the toughening agent is a polyether-type medical toughening agent.

3. The antibacterial medical primary packaging coated paper according to claim 1, characterized in that, The surface antibacterial protective adhesive layer comprises, by weight, the following: Waterborne polyurethane resin: 50-60 parts; Compound antibacterial agent: 4-8 parts; Pore-forming dispersant: 2-3 parts; Film-forming aid: 1-2 parts; Deionized water: 18-22 parts; The composite antibacterial agent is composed of nano titanium dioxide, chitosan and silver ion slow-release antibacterial powder in a mass ratio of (2-4):(4-6):(1-3).

4. The antibacterial medical primary packaging coated paper according to claim 3, characterized in that, The pore-forming dispersant is a gel material supported on an azo compound, and the mass ratio of the gel material to the azo compound is (3-5):

1.

5. The antibacterial medical primary packaging coated paper according to claim 1, characterized in that, The coating amount of the bottom modified sealant layer is 8-12 g / ㎡, and the coating amount of the top antibacterial protective adhesive layer is 3-5 g / ㎡.

6. A method for preparing an antibacterial medical primary packaging coated paper as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Dry the medical breathable base paper substrate at 60-70℃ for 30 minutes; S2. After mixing and stirring the modified acrylic resin, medical hot melt elastomer, and deionized water, add the crosslinking agent and toughening agent, and then perform high-speed homogenization and emulsification. S3. After mixing waterborne polyurethane resin and deionized water, film-forming aid and composite antibacterial agent are added, and then a gel-loaded azo compound as a pore-forming dispersant is added. The gel-loaded azo compound forms an electrostatic adsorption complex with chitosan, and is then dispersed at high speed and defoamed by ultrasonication. S4. First, apply the base layer sealant and pre-dry and cure it; then apply the top layer antibacterial sealant. S5. Heat treatment of the coated semi-finished product at 50-70℃ to break the electrostatic adsorption between the azo compound and chitosan, so that the azo compound is uniformly released and dispersed in the adhesive layer, and at the same time, a microporous structure is formed. S6. First cure at 90℃ for 20 minutes, then cure at 120℃ for 15 minutes; S7. Perform dust-free cooling, electrostatic dust removal, and surface smoothing treatment on the cured coated paper.

7. The preparation method according to claim 6, characterized in that, In step S2, the high-speed homogenization emulsification speed is 8000 r / min and the time is 20 minutes.

8. The preparation method according to claim 6, characterized in that, In step S5, the heating treatment time is 5-15 minutes.

9. The preparation method according to claim 6, characterized in that, In S7, the surface leveling treatment is carried out using a contact hot press roller or an air flotation leveling device.

10. The application of the antibacterial medical primary packaging coated paper prepared by any one of claims 7 to 9 in the preparation of sterilization packaging materials for medical devices.